2020
DOI: 10.1007/s00381-020-04645-z
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in newborns with hypoxic-ischemic encephalopathy treated with therapeutic hypothermia

Abstract: The aim of the presented study was to evaluate the differences between selected biochemical markers in infants with moderate or severe hypoxic-ischemic encephalopathy (HIE) and their impact on patient prognosis. Methods A total of 57 cooled newborns were divided into groups according to Sarnat staging of HIE (A, moderate vs. B, severe). The differences between groups were evaluated depending on the mode of delivery, pregnancy and labor complications, gestational age at birth, birth weight, and Apgar score at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Hypoxic-ischemic encephalopathy can result in severe neurodevelopmental disability and mortality in, respectively, 24.9% and 34.1% of cases [ 13 ]. Further observations of infants suffering from perinatal asphyxia showed that 27–33% of them aged 6–7 years will have features of intellectual disability [ 14 ]. This brain damage is secondary to an episode of hypoxia-ischemia as well as reoxygenation-reperfusion following resuscitation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxic-ischemic encephalopathy can result in severe neurodevelopmental disability and mortality in, respectively, 24.9% and 34.1% of cases [ 13 ]. Further observations of infants suffering from perinatal asphyxia showed that 27–33% of them aged 6–7 years will have features of intellectual disability [ 14 ]. This brain damage is secondary to an episode of hypoxia-ischemia as well as reoxygenation-reperfusion following resuscitation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reports of biomarkers being correlated with MRI-indicated lesions are limited. Lactate may be beneficial for predicting severe MRI-indicated lesions that are typically correlated with poor neurodevelopmental outcomes at 1 year old [ 15 , 27 ]. Neurodevelopmental outcomes at 1 year old are closely related to the two weeks of MRI findings after birth for neonatal patients with stage II and stage III HIE [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…DIC in the neonate, most commonly occurs in the setting of perinatal asphyxia, but can be due to sepsis and perinatal acquired infections, respiratory distress syndrome and meconium aspiration ( 14 , 137 , 138 ). Severe perinatal asphyxia can cause significant hypoxic brain injury and multi-organ failure, including hepatic damage ( 139 , 140 ). Hypoxic hepatic damage can lead to reduced production of coagulation factors and hypofibrinogenemia ( 140 ).…”
Section: Neonates and Hypofibrinogenemiamentioning
confidence: 99%